The Macroeconomic Impacts of Natural Disasters in the Caribbean : 360° Resilience Background Paper - Strobl, Eric (World Bank, Washington, DC, 2021)
This paper provides a review and assessment of the current literature on the macroeconomic impact of natural disasters in the Caribbean, including other non-Caribbean studies that may have implications for it. It also discusses, in view of existing studies, what factors may make Caribbean economies more resilient to these extreme events, as well as whether there are damage thresholds beyond which recovery will be more difficult. Finally, recommendations are provided for future data collection and research that might provide further light on the issues.